PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA MQ GUEST HOUSE BANDUNG - Trustorini Handayani (JURISMA : Jurnal Riset Bisnis & Manajemen, 2012)
ABSTRAKMQ Guest House is company which active in hotel service. It has also incorporated the introduction on â€œManagement Qolbuâ€ concept. MQ Guest House in a few last month experiences downdraft of number of lodging costumers estimable resulted from the competitor in region north Bandung. But MQ Guest House has excellence service that is having attention to customer or client by listening by critics, suggestion, and sigh felt by customer or client. Hence writer interests to do elite with headline â€œThe Influence of Service Quality on the Customer Loyalty of MQ Guest House Bandungâ€.The purposes of this research is to know the respondents conceptions to the service quality of MQ Guest House Bandung, to know the customer loyalty at MQ Guest House Bandung, and to know the influence of services quality to the customer loyalty of MQ Guest House Bandung.The method that us in this research is explanatory survey method, this research kind is descriptive and verivicative analysis, with using sample from population in company by 100 respondent with using questioner as data collection tool, and to make it simple in analyze the data, writer used SPSS 13 for Windows.The result of this research showed that r is 0,873%, this show that there a strong relation, one way and significant between service quality and customer loyalty. While determination coefficient resulted 76,2% and rest is 23,78% influenced by in other factor such as a price, competitor, and many other. This showed is that if service quality increased so customer loyalty also increased at MQ Guest House Bandung.Keyword: Service Quality, Customer Loyalty